Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/ptr.5776
|View full text |Cite
|
Sign up to set email alerts
|

White Ginseng Protects Mouse Hippocampal Cells Against Amyloid-Beta Oligomer Toxicity

Abstract: Amyloid-beta oligomer (AβO) is a soluble oligomer form of the Aβ peptide and the most potent amyloid-beta form that induces neuronal damage in Alzheimer's disease. We investigated the effect of dried white ginseng extract (WGE) on neuronal cell damage and memory impairment in intrahippocampal AβO (10 μM)-injected mice. Mice were treated with WGE (100 and 500 mg/kg/day, p.o.) for 12 days after surgery. WGE improved memory impairment by inhibiting hippocampal cell death caused by AβO. In addition, AβO-injected m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
(53 reference statements)
0
14
0
Order By: Relevance
“…In addition, the AβO-injected mice treated with WGE exhibited a restoration of reduced synaptophysin and ChAT intensity, and lower levels of ionized calcium-binding adaptor molecule 1 in the hippocampus compared with those of the vehicle-treated controls. These results suggest that WGE reverses memory impairment in AD by attenuating neuronal damage and neuroinflammation in the hippocampus of mice injected with AβO (42).…”
Section: Ginsenosides and The Acetylcholine Levelmentioning
confidence: 72%
“…In addition, the AβO-injected mice treated with WGE exhibited a restoration of reduced synaptophysin and ChAT intensity, and lower levels of ionized calcium-binding adaptor molecule 1 in the hippocampus compared with those of the vehicle-treated controls. These results suggest that WGE reverses memory impairment in AD by attenuating neuronal damage and neuroinflammation in the hippocampus of mice injected with AβO (42).…”
Section: Ginsenosides and The Acetylcholine Levelmentioning
confidence: 72%
“…The extracts were orally administered at a dose of 100 mg/kg every other day for 4 weeks (Figure S2). The dose was determined based on previous studies examining the effects of RGE using animal models [96,97,98]. The experiment was conducted in three groups: (1) WT+vehicle ( n = 6), (2) 5XFAD+vehicle ( n = 7), and (3) 5XFAD+RGE ( n = 6).…”
Section: Methodsmentioning
confidence: 99%
“…It has been revealed that ginsenoside contents of WG are Rg 1-2 , Rb 1-3 , and R c-f [14, 15]. WG has been reported to have therapeutic effects on hyperlipidemia, obesity, cancer, and Alzheimer's disease [1418]. Nevertheless, antidepressant effects of WG in an animal model of menopausal depression have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%